Alcohol Consumption Is a Modifiable Risk Factor for Breast Cancer: Are Women Aware of This Relationship? - Agabio, Roberta; Madeddu, Clelia; Contu, Paolo; Cosentino, Sofia; Deiana, Monica; Massa, Elena; Mereu, Alessandra; Politi, Carola; Sardu, Claudia; Sinclair, Julia M A (Alcohol and alcoholism (Oxford), 2022)
Abstract Aims Despite alcohol consumption being a dose-dependent risk factor for breast cancer, a recent study conducted in the UK found <20% of women attending breast screening programmes were aware of this relationship and proposed proper information campaigns need to be conducted. We aimed to investigate the awareness of this relationship among a related sample of Italian women to evaluate whether similar information campaigns should also be conducted in Italy. Methods The questionnaire used by the UK study was translated into Italian, slightly modified for the Italian context, validated and submitted to a sample of Italian women. Results Overall 507 women were interviewed. Among them, 160 were classified as breast cancer screening attenders (SG), 44 as symptomatic breast clinic attenders (CAG) and 303 as non-screening group (NSG). Alcohol was correctly identified as a risk factor for breast cancer by 16.9, 11.4 and 14.9% of participants of SG, CAG and NSG, respectively without differences between the three groups. Despite the methodological differences, the rates of participants who correctly identified alcohol as a risk factor among women attending breast screening programmes were surprisingly similar between the study conducted in UK (15.7%) and the present study (16.9%). Conclusion The results of the present study confirm the limited awareness of the relationship between alcohol consumption and risk of developing breast cancer among women and suggest the urgent need to conduct proper awareness-raising campaigns to counter this in the Italian female population. Short summary: Less than 20% of women across different populations were aware of the relationship between alcohol consumption and risk of developing breast cancer. There is an urgent need to conduct proper awareness-raising campaigns in the Italian female population.